Microbes in Food and Health - Garg, Neelam; Abdel-Aziz, Shadia Mohammad; Aeron, Abhinav (Springer International Publishing : Imprint: Springer, 2016)
This book gives an overview of the physiology, health, safety and functional aspects of microorganisms present in food and fermented foods. A particular focus is on the health effects of probiotics and non-dairy functional foods. The book deals also with microbes that cause food spoilage and produce toxins, and the efficiency of edible biofilm in the protection of packaged foods. Several chapters are devoted to the occurrence of Listeria pathogens in various food sources. Further topics are fortified foods, the role of trace elements, and the preservation of food and extension of food shelf life by a variety of measures.